2021
DOI: 10.3390/cancers13071724
|View full text |Cite
|
Sign up to set email alerts
|

The Tumour Vasculature as a Target to Modulate Leucocyte Trafficking

Abstract: The effectiveness of immunotherapy against solid tumours is dependent on the appropriate leucocyte subsets trafficking and accumulating in the tumour microenvironment (TME) with recruitment occurring at the endothelium. Such recruitment involves interactions between the leucocytes and the endothelial cells (ECs) of the vessel and occurs through a series of steps including leucocyte capture, their rolling, adhesion, and intraluminal crawling, and finally leucocyte transendothelial migration across the endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 221 publications
(173 reference statements)
0
6
0
Order By: Relevance
“… 37–39 We found that OAd-MUC16-BiTE promotes the secretion of pro-inflammatory factors by T cells and decreases anti-inflammatory factors. The increase in chemokine levels 40 and the normalization of blood vessels 41 promote the transport of T cells to the tumor. In line with this, we found that after OAd-MUC16-BiTE treatment, tumors expressed higher levels of chemokines and lower angiogenesis factor, which promotes more CTL infiltration.…”
Section: Discussionmentioning
confidence: 99%
“… 37–39 We found that OAd-MUC16-BiTE promotes the secretion of pro-inflammatory factors by T cells and decreases anti-inflammatory factors. The increase in chemokine levels 40 and the normalization of blood vessels 41 promote the transport of T cells to the tumor. In line with this, we found that after OAd-MUC16-BiTE treatment, tumors expressed higher levels of chemokines and lower angiogenesis factor, which promotes more CTL infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of immune cells into the TME is known to influence tumour progression ( 19 ). A systematic analysis of the relationship between tumour immune infiltration and hub genes can throw light on the mechanism of tumour immune escape and facilitate the development of new biomarkers and therapeutic strategies.…”
Section: Methodsmentioning
confidence: 99%
“…These pathways play important roles in the immune and inflammatory responses, cell migration, proliferation, and survival, and are critical in cancer progression and metastasis. 30 32 Certain chemokines like CCL20, PI3K/Akt, and Ras have been shown to be involved in the progression of GPLs. 33 – 35 Overall, these intersecting genes may be involved in LGIN to GC progression by regulating immune cell activity and cancer-related pathways.…”
Section: Discussionmentioning
confidence: 99%